Development of Symphysio Fundal Height Curve (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Objective: To Develop a symphysio fundal height(SFH) curve of pregnant women from 20 weeks of pregnancy onwards; and to find out the relationship of fundal height with different variables.Methodology: A cross-sectional hospital based study was conducted from 1st january 2010 to 31st December 2010 on 159 patients with gestation age less than 20 weeks at entry in the OPD of Department of Obstetric and Gynaecology, Shaheed Suhrawardy Medical College & Hospital, Shere-e Bangla Nagar, Dhaka,Bangladesh. All the patients were followed up till delivery.Results: The measurements of SFH obtained on the basis of 10, 50th and 90th percentiles and the rate of growth of SFH was approximately 5 mm per week from 24 weeks to 36 weeks and thereafter it was 5-6 mm per week till 40 weeks.Patients with higher socioeconomic class had higher symphysio fundal height.SFH is less in younger subjects. SFH increases with increased height,weight,gestational age,gravidity of mothers and birth weight of the baby.Multiparous was predominant and more than one third (34.6%) of the study patients height belonged to 1.51 - 1.60 meters. The mean±SD gestational age was 39.2±1.4 weeks with range from 28 to 41 weeks. Low birth weight was found 17.0% and the mean±SD birth weight was 2.8±0.4 kg with range from 1.9 to 3.8 kg.Bangladesh J Obstet Gynaecol, 2017; Vol. 32(1): 20-24